2003
DOI: 10.1007/s00330-002-1583-z
|View full text |Cite
|
Sign up to set email alerts
|

Results of the safety and efficacy of iobitridol in more than 61,000 patients

Abstract: We present results of a postmarketing surveillance study with iobitridol (Xenetix, Sulzbach, Germany) in more than 61,000 patients from 1996 until 2000. The purpose of this study was the assessment of safety and diagnostic efficacy of the non-ionic contrast agent iobitridol in the setting of a post-marketing surveillance study. Iobitridol (Xenetix) has been registered in Germany since 1996. Between 1996 and 2000 207 radiologists have documented in a questionnaire the routine use of Xenetix in 61,754 patients t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
(12 reference statements)
5
21
1
Order By: Relevance
“…The frequency of adverse reactions in our study is comparable with previously reported investigations in large radiological patient populations [9,10] . The observation that female patients in this study suffered significantly more adverse events than males is likely to be due to a higher prevalence of allergies in females.…”
Section: Discussionsupporting
confidence: 82%
“…The frequency of adverse reactions in our study is comparable with previously reported investigations in large radiological patient populations [9,10] . The observation that female patients in this study suffered significantly more adverse events than males is likely to be due to a higher prevalence of allergies in females.…”
Section: Discussionsupporting
confidence: 82%
“…The findings of the present study showed that the patients aged 18-29 (0.42%), 30-39 (0.40%), 40-49 (0.43%) and 50-59 (0.43%) years were with the highest incidence rate of ADRs, which was in accordance with the relatively high incidence rate in patients aged 18-50 years that was reported in previous studies, 3,9,10 whereas the ones aged 70-79 (0.19%) years were with the lowest incidence rate of ADRs, which was not in accordance with the highest incidence rate in patients aged 20-29 years reported by Khachman et al 11 The results of the present study showed no ADRs in the patients aged below 1 year, which was in accordance with the findings of Callahan et al 12 The low incidence rate in this age group could be associated with the insufficient immune responses in infants, could not identify the mild and moderate ADRs and difficulties in communication; in addition, some infants were examined under monitored anaesthesia care or oral intake of 10% chloral hydrate, which caused mild and moderate ADRs not easily identified. 13 Patients aged 18-59 years had a relatively high incidence rate of ADRs, which could be associated with the fact that the patient in these age groups had relative high pressure, hypochondriasis, tended to actively express themselves, and had relatively high immune activity 14 and thus increased the reactiveness of the body. 4 Among the 14 cases with severe ADRs, 12 (86%) were aged more than 50 years, while 2 were aged more than 40 years, suggesting that the risk of developing severe ADRs was higher in patients with moderate or advanced ages, which could also be associated with the relatively high prevalence of cardiopulmonary diseases and poorer basic conditions in these patients, which increased the risk of developing ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of the appearance of allergic reactions depending on age was described by Petersein et al [19], Kopp et al [1] and Katayama et al [20]. According to their studies, side effects were more common in patients in the 18-50 age group than in the 50-80 age group and older.…”
Section: Discussionmentioning
confidence: 98%
“…The highest frequency was reported in young female patients of 18-30. Petersein et al [19] pointed out that in young people the functioning of the immune system is better and explained the side effects in terms of a more or less efficient immune response.…”
Section: Discussionmentioning
confidence: 99%